Theology disrupted by the challenge of refugee children - Kritzinger, Johannes (HTS teologiese studies, 2016)
This article focuses on the plight of refugee children and families and takes the form of a dialogue between an academic theologian and a community activist who works for an organisation assisting refugees in Tshwane. This article is structured according to a sixdimensional ‘pastoral cycle’ that explores agency, contextual understanding, ecclesial scrutiny, interpreting the tradition, discernment for action and spirituality. In each section the views of the two authors are juxtaposed, rather than merged into a single voice. This article concludes with a reflection on the method followed.